DESIGN OF REMOTING TELESCOPE IN OBSERVATORIUM ILMU FALAK UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Ajraini Nazli; Hariyadi Putraga; Muhammad Hidayat; Arwin Juli Rakhmadi (Proceeding International Seminar of Islamic Studies, 2022)
Disruption of technology is able to provide wider access in astronomy field. One of them through access the observation by using various remoting intruments. The easier way to use instrument particularly telescopes will facilitate data collection for both amateur and professional astronomers. In addition, the open access can increase public interest toward astronomy. Therefore, Observatorium Ilmu Falak Universitas Muhammadiyah Sumatera Utara (OIF UMSU) designs and develops remote telescope service based on the internet network. The system controls telescope via computer. The system consists the Astronomical Imaging System (AIS) and Human-machine Interface (HMI). The telescope designed with remote system is the Bresser Messier AR-152L (Diameter 152 mm dan focal ratio f/7,9) and Losmandy G11 Gemini mount. The system uses two computers. First computer is connected to the telescope devices and the second is used for remote control. The remoting telescope requires a stellarium, sharpcap, and teamviewer, as well as WiFi connection. The research is expected to help and give solution for researchers restricted by access and distance to observe celestial object using remoting telescope.Keywords: Telescope, Remote, OIF UMSU